Cholesterol 25-Hydroxylase Inhibits Porcine Reproductive and Respiratory Syndrome Virus Replication through Enzyme Activity-Dependent and -Independent Mechanisms - Ke, Wenting (J Virol, 2017)
Cholesterol 25-hydroxylase (CH25H) has recently been identified as a host restriction factor that exerts antiviral effects by catalyzing the production of 25-hydroxycholesterol (25HC). CH25H can be rapidly induced upon infection with some viruses. Porcine reproductive and respiratory syndrome virus (PRRSV), an arterivirus, has ranked among the most important swine pathogens since it was discovered in the late 1980s. In this study, we found that PRRSV infection significantly downregulated the expression of CH25H in cells by a so-far unknown mechanism, suggesting that CH25H exerts antiviral activity against PRRSV. Indeed, overexpression of CH25H inhibited PRRSV replication, whereas knockdown of CH25H by short interfering RNA (siRNA) promoted PRRSV infection. The anti-PRRSV effect of 25HC operates via inhibition of viral penetration. Interestingly, a CH25H mutant (CH25H-M) lacking hydroxylase activity still inhibited PRRSV infection. Screening using a yeast two-hybrid system followed by coimmunoprecipitation and immunofluorescence colocalization analyses confirmed that both CH25H and CH25H-M interact with the nonstructural protein 1 alpha (nsp1α) of PRRSV. Unexpectedly, the expression of nsp1α decreased following coexpression with CH25H or CH25H-M. Detailed analyses demonstrated that CH25H/CH25H-M could degrade nsp1α through the ubiquitin-proteasome pathway and that site K169 in the nsp1α protein is the key site of ubiquitination. Taken together, our findings demonstrate that CH25H restricts PRRSV replication by targeting viral penetration as well as degrading nsp1α, revealing a novel antiviral mechanism used by CH25H. IMPORTANCE PRRSV has been a continuous threat to the global swine industry, and current vaccines are insufficient to provide sustainable control. CH25H has been found to exert a broad antiviral effect; thus, it is an attractive target for the development of anti-PRRSV drugs. Here, we demonstrate that CH25H is an interferon-stimulated gene that is highly expressed in porcine alveolar macrophages. CH25H exerts its anti-PRRSV effect not only via the production of 25HC to inhibit viral penetration but also by degrading viral protein through the ubiquitin-proteasome pathway, suggesting that CH25H is a candidate for the development of antiviral therapeutics. However, PRRSV infection appears to actively decrease CH25H expression to promote viral replication, highlighting the complex game between PRRSV and its host.